Self-Regulated Learning Development: Students’ Perception of Explicit Instructional Support in Online Learning - Mallipa, Imelda; Murianty, Riana (International Journal of Education, 2021)
Students’ ability to regulate their own learning is the key to learning in the twenty-first century, particularly in online learning environments during a pandemic situation. Studies have indicated the significant contribution of Self-regulated learning (SRL) to academic success. This current study sought to understand and describe students’ perceptions and behavior in response to online teaching instructions designed in the light of SRL theories. The instructional support was designed following the principles of SRL from a social cognitive researcher. Twenty-five undergraduate students participated in this study. The data was obtained from questionnaires, tests, and observation. The learning activities were conducted in an E-learning platform provided by the university, Google Forms, and virtual meetings. The results from the questionnaire showed that explicit instructional supports effectively encouraged students to employ SRL skills in their learning process. Albeit, the data from observation described that only some of the SRL skills were acquired and developed during online instructions, and some skills still needed time to develop due to the fact that students were at the first level of SRL. The students in this study still need more exercises and practices to support them in continually developing their SRL skills. In future interventions, students should be trained to acquire self-assessment and task-selection skills. This study suggests providing explicit instructional support to assist university students with low-level or minimal SRL capacity in developing SRL capacity.